Architectured bimetallic laminates by roll bonding: bonding mechanisms and applications. (July 2014) - Kaabi, A.; Bienvenu, Y.; Ryckelynck, D.; Prévond, L.; Pierre, B.
<x content-type="archive" xml:space="preserve">Abstract</x> Manufacturing of bimetallic laminates (<2 mm) with an internal architecture by roll bonding allows to obtain a compromise of conflicting properties. Two applications are considered: copper–steel–copper sheets for high power electronic component substrates and lightweight aluminium–steel–aluminium laminates for structural, electromagnetic applications in power generation and for electromagnetic compatibility. They have in common an architecture, with three-dimensional percolating networks of two metals produced with a sufficient precision. The bonding mechanisms are investigated through microstructural and thermomechanical characterisation of the assemblies produced. Roll bonding fills the voids in a central component by plastic deformation and creates the bonds by cold welding. It may be followed or preceded by surface and heat treatments with the objective to improve the cold welding and to relieve the internal stress state. Architectural rules to optimise the properties of the two-phase laminates in view of the applications may be guided by finite element models combining physical and thermomechanical aspects.